P90 Neuropsychiatric disorder and Montelukast: a case report and VigiBase® analysis. Issue 6 (17th May 2019) - Scholz, I; Banholzer, S; Haschke, M
Abstract : Learning objective: Recognize neuropsychiatric symptoms as possible adverse drug reactions (ADR) associated with the leukotriene receptor antagonist Montelukast in children Clinical Case: An 11-year-old boy suffering from asthma presented to his pediatrician with an acute onset of nervousness, restlessness and irritability. The teacher noticed a decline in school performance with a reduced attention span. The patient had been treated with Salbutamol (Ventolin®) and Salmeterol/Fluticasone (Seretide®) for the last few years. A treatment with Montelukast chewable tablets was started four months ago. The ADR was reported to the Regional Pharmacovigilance Centre (RPVC) Bern. The termination of the therapy with Montelukast lead to an amelioration of the symptoms. According to the WHO-UMC Causality Categories, 1 the causality of Montelukast and the described symptoms was classified as 'probable'. The causality of the comedication was considered 'unlikely' as it had been used for several years without complications. After work-up at the RPVC, the case was reported anonymously to the National Pharmacovigilance Center of the Swiss Agency for Therapeutic Products Swissmedic. Discussion: Montelukast is a cysteinyl-leukotriene type 1-receptor antagonist used in the treatment of bronchial asthma in adults and children. Psychiatric disorders such as agitation, psychomotor hyperactivity (including irritability and restlessness), disorders of attention and memory impairment (and others) are listed as known ADRs of Montelukast. 2 3 The WHO pharmacovigilance database VigiBase® lists a total of 20'897 ADR reports for Montelukast, of which 4'705 (22.5%) refer to nervous system disorders and 6'828 (32.7%) to psychiatric disorders. Within the group of nervous system disorders 256 (5.4%) reports of psychomotor hyperactivity, 232 (4.9%) reports of disturbance in attention and 91 (1.9%) reports of memory impairment were recorded. 4 The most common symptoms in the group of psychiatric disorders are depression (1'311, 19.2%) and aggressive behavior (1'175, 17.2%). If psychiatric ADRs occur, the risks and benefits of Montelukast should be reassessed. References: The use of the WHO-UMC system for standardised case causality assessment. Available from:https://www.who.int/medicines/areas/quality_safety/safety_efficacy/WHOcausality_assessment.pdf Marchand MS, Jonville-Bera AP, Autret-Leca E, [Psychiatric disorders associated with montelukast: data from the National Pharmacovigilance Database]. Arch Pediatr 2013;20(3):269–73. Aldea Perona A, Garcia-Saiz M, Sanz Alvarez E. Psychiatric disorders and montelukast in children: A disproportionality analysis of the vigibase((R)). Drug Saf 2016;9(1):69–78. Disclosure(s): Nothing to disclose